Reliability and discriminative ability of a modified Wingate rowing test in 12- to 18-year-old rowers - Mikulic, P.; Emersic, D.; Markovic, G. (Journal of Sports Sciences, 2010)
We evaluated (1) the test-retest reliability of the Wingate test conducted on a rowing ergometer, and (2) the sensitivity of this test in determining the differences in performance attained by 12- to 18-year-old rowers. Altogether, 297 male rowers aged 12.0-18.9 years (mean ± s: 14.8 ± 1.7) completed a maximal 30-s test on a rowing ergometer, and 80 rowers representing all age groups were retested after 5-7 days. No change was evident in participants' performance in terms of mean power output (P = 0.726; Cohen's d = 0.04), maximal power output (P = 0.567; Cohen's d = 0.06), and minimum power output (P = 0.318; Cohen's d = 0.11) in the second test. The intra-class correlation coefficients were high (=0.973) and coefficients of variation were low (=7.3%). A series of analyses of variance were used to compare the performances among 12- to 18-year-old rowers, and age-related increases in performance were evident (P < 0.001; Cohen's d = 1.91-1.96). The age-related increases in performance were similar, although reduced, when the effects of body mass were partitioned out when using analysis of covariance (P < 0.001; Cohen's d = 0.82-0.85). The results suggest that: (1) the described test is reliable and can be used for maximal-intensity exercise assessment in youth rowing, and (2) it discriminates performance among 12- to-18-year-old rowers.